Don Ricardo Palma, today - Varillas Montenegro, Alberto (2019)
It is very common for Ricardo Palma to be presented as an elderly writer who wrote the Peruvian Traditions. This work is destined to remember that today we have all the necessary information about the origin, birth, school studies, and moving youth of Palma. At present, we know the detail of his time in the Peruvian Navy, his adventures as a liberal journalist and his two exiles, his long life as a correct publicofficial. We also know that with the success of his more than 500 traditions, even if he would not have created a new genre or would not have rescued from anything the National Library, he became one of the most valuable promoters of the Peruvian reaction after the War of the Pacific.